Lee Kuan Yew's strategic thought - Ang, Cheng Guan. (New York : Routledge, 2013)
"Lee Kuan Yew, as the founding father of independent Singapore, has had an enormous impact on the development of Singapore and of Southeast Asia more generally. Even in his 80s he is a key figure who continues to exert considerable influence from behind the scenes. This book presents a comprehensive overview of Lee Kuan Yew's strategic thought. It charts the development of Singapore over the last six decades, showing how Lee Kuan Yew has steered Singapore to prosperity and success through changing times"--Provided by publisher.
From the 1950s to the mid-70s -- 1975-1979 -- The 80s decade -- The 90s decade -- The new millennium.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Lee, Kuan Yew, -- 1923-; Singapore -- Foreign relations; Singapore -- Politics and government; Electronic books